Higher vascular endothelial growth factor‐C concentration in plasma is associated with increased forearm capillary filtration capacity in breast cancer‐related lymphedema. Issue 6 (9th June 2015) - Jensen, Mads Radmer; Simonsen, Lene; Karlsmark, Tonny; Lanng, Charlotte; Bülow, Jens
Abstract: Breast cancer‐related lymphedema (BCRL) is a frequent, chronic and debilitating swelling that mainly affects the ipsilateral arm and develops as a complication to breast cancer treatment. The pathophysiology is elusive opposing development of means for prediction and treatment. We have earlier shown that the forearm capillary filtration coefficient (CFC) is increased bilaterally in BCRL. In this study, we aimed to elucidate if increased CFC is associated with low‐grade inflammation and/or vascular endothelial growth factor‐c (VEGF‐C) signaling. Fourteen patients with unilateral BCRL and nine matched breast cancer controls without BCRL participated. Forearm CFC was measured by venous congestion strain gauge plethysmography, and suction blisters were induced medially on the upper arms. Concentrations of 17 selected cytokines, VEGF‐C, and total protein were measured in blister fluid and in plasma. Forearm CFC was higher bilaterally in BCRL subjects ( P ≤ 0.036). No differences between forearms were found in either group. Plasma VEGF‐C concentrations were significantly higher in the BCRL subjects ( P < 0.001). In BCRL subjects, monocyte chemotactic protein 1 (MCP‐1) ( P = 0.009) and total protein ( P = 0.035) concentrations were higher in blister fluid from edematous arms compared with nonedematous arms. No differences were found in interstitial cytokine or total protein concentrations between arms in control subjects. Higher plasma concentration of VEGF‐C is a possible cause of bilaterally increased forearm CFC in BCRL subjects. Interstitially increased MCP‐1 levels may augment local microvascular protein permeability in BCRL. Abstract : Breast cancer‐related lymphedema is a common and debilitating complication to breast cancer treatment with poorly elucidated pathophysiology. In this paper, we show that a bilateral increase in forearm capillary filtration capacity is associated with higher concentration of vascular endothelial growth factor C in plasma in subjects with breast cancer‐related lymphedema compared with matched controls. Furthermore, we found higher concentrations of monocyte chemotactic protein 1 and total protein in suction blister fluid from edematous arms compared to the paired nonedematous arms in subjects with breast cancer‐related lymphedema.